A proposed framework for addressing supervisee-supervisor value conflict. Issue 2 (3rd July 2017) - Dunn, Rose; Callahan, Jennifer L.; Farnsworth, Jacob K.; Watkins, C. Edward
ABSTRACT: Value conflicts between supervisees and supervisors can adversely affect supervisee development, service provision, and the supervision relationship. However, the role of value conflicts in supervision has been minimally considered. Building on the Farnsworth and Callahan (2013) model for addressing client-clinician value conflict, we propose a supervision-specific framework to help supervisors and supervisees navigate value conflicts that emerge during supervision. The proposed framework consists of three steps: (a) detection of value conflict in supervision; (b) identification and articulation of value conflicts; and (c) determination of appropriate recommendations for supervisees. Neither punitive nor corrective in purpose, the model is eminently exploratory and educational in nature.